1991
DOI: 10.2307/1940583
|View full text |Cite
|
Sign up to set email alerts
|

Density‐Dependent Growth, Body Condition, and Demography in Feral Donkeys: Testing the Food Hypothesis

Abstract: The food hypothesis of population regulation was tested using two predation—free populations of feral donkeys in tropical northern Australia. Growth, body condition, and age—specific rates of fecundity and mortality were compared between the two populations. One of the populations was roughly one—half the density of the other, following an experimental reduction 3—4 yr previously. Fecundity was high and independent of density, with >70% of mature females pregnant in both populations. Age at maturity and juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 32 publications
1
87
1
Order By: Relevance
“…Resource availability, often limited by high population density, has been shown to be the major driver behind body size variation in several extant mammal species, such as reindeer (Skogland, 1983), feral donkeys (Choquenot, 1991) and roe deer (Toïgo et al, 2006). Wolverton et al (2009) were able to show that there is a negative correlation between individual body size and population density in the extant white-tailed deer (Odocoileus virginianus) in North America, and that body size variation in that species is better explained by geographic differences in food availability than by thermoregulatory benefits suggested by "Bergmann's Rule".…”
Section: Body Size and Synthesismentioning
confidence: 99%
“…Resource availability, often limited by high population density, has been shown to be the major driver behind body size variation in several extant mammal species, such as reindeer (Skogland, 1983), feral donkeys (Choquenot, 1991) and roe deer (Toïgo et al, 2006). Wolverton et al (2009) were able to show that there is a negative correlation between individual body size and population density in the extant white-tailed deer (Odocoileus virginianus) in North America, and that body size variation in that species is better explained by geographic differences in food availability than by thermoregulatory benefits suggested by "Bergmann's Rule".…”
Section: Body Size and Synthesismentioning
confidence: 99%
“…Convincing evidence has already emerged in support of a link between the FMH and migration: migratory ungulates' access to earlier-stage plant phenology can be prolonged relative to that of residents (Pettorelli et al 2005a;Hebblewhite et al 2008;Sawyer and Kauffman 2011), which leads to higher forage quality for migrants (Hebblewhite et al 2008;Hamel et al 2009). As a consequence of access to better forage, migrants are heavier than resident individuals (Albon and Langvatn 1992), and body condition is tightly linked with fitness components in ungulates (White 1983;Choquenot 1991;Gaillard et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Winter food shortage results in mortality by depressing birth weights and delaying dates of birth (Blaxter and others 1981, Thorne and others 1976, Verme 1969. In fact, CluttonBrock and others (1987,1988) and Choquenot (1991) concluded that juvenile mortality, through densityinduced food shortage effects on birth weight and date, was the key factor regulating populations of red deer and feral donkeys, respectively. Experimental reduction in density of Rocky Mountain goats led to decreased age at first reproduction and to an increase in the number of young per reproducing female (Houston and Stevens 1988).…”
Section: Predicted Feedback Effects Of Herbivory On Large Ungulate Pomentioning
confidence: 99%